STRATEGIC ANALYSIS OF THE APPLICATION OF THE AT-TIKRAR METHOD IN SHARPENING THE TAHFIDZ AN-NADZM ALFIYAH IBN AL-MĀLIK AT MA’HAD ALY ISLAMIC BOARDING SCHOOL (STUDY AT MAHAD ALY PONDOK PESANTREN ANNUR 2) - Munadi, Moh. Robith; Syahansyah, Zulfan; Husni, Muhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study examines the application of the tikrār (repetition) tradition in memorizing Nadzm Alfiyah Ibnu Mālik at Mahad Aly Pondok Pesantren Annur 2. Purpose: The main objectives of the research are to describe the models of tikrār implementation, analyze supporting and hindering factors, and map the experiences of students and their implications for the design of memorization programs. Three main models of tikrār were identified: (1) gradual repetition of each verse independently, (2) collective repetition led by the class leader, and (3) full target repetition according to the semester goal. Method: The CIPP evaluation shows that this strategy is suitable for Mahad Aly students, supported by adequate human resources and facilities, although it faces challenges such as time limitations, nighttime fatigue, and fluctuating motivation. SWOT-TOWS analysis reveals the main strengths of a consistent program structure and strong communal culture, while its weaknesses include method monotony and a lack of retrieval practice variation. Implication: Practical implications include designing a realistic schedule, developing monitoring tools based on logbooks, incorporating spaced retrieval activities, and providing time management training. Conclusion: This study emphasizes the importance of synergy between pesantren traditions and modern cognitive approaches to enhance the effectiveness of memorization programs.